0.1x-0.3(6-3x)=-0.6(x-5)

Simple and best practice solution for 0.1x-0.3(6-3x)=-0.6(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.1x-0.3(6-3x)=-0.6(x-5) equation:



0.1x-0.3(6-3x)=-0.6(x-5)
We move all terms to the left:
0.1x-0.3(6-3x)-(-0.6(x-5))=0
We add all the numbers together, and all the variables
0.1x-0.3(-3x+6)-(-0.6(x-5))=0
We multiply parentheses
0.1x+0.9x-(-0.6(x-5))-1.8=0
We calculate terms in parentheses: -(-0.6(x-5)), so:
-0.6(x-5)
We multiply parentheses
-0.6x+3
Back to the equation:
-(-0.6x+3)
We add all the numbers together, and all the variables
x-(-0.6x+3)-1.8=0
We get rid of parentheses
x+0.6x-3-1.8=0
We add all the numbers together, and all the variables
1.6x-4.8=0
We move all terms containing x to the left, all other terms to the right
1.6x=4.8
x=4.8/1.6
x=2+1/1

See similar equations:

| |4x+9|=8 | | 0.6x-0.5(30+x)=-0.4(30) | | x^2-3x=10=0 | | 0=x^2+7x+2 | | F(-2)=4x^2+3x+8 | | b=1+2b=28 | | -3d-6=2 | | -15=p+2 | | 5.8m–3.7m–8.6=6.1 | | x/2-1/3=x/3-1/5 | | -6w+1=-2 | | 11-2t+3t=-5-3 | | 4x^2-24x+60=0 | | 9x-4x(x-2)=x+2 | | 5.8m-3.7m-8.9=6.1 | | (3p+5)/5=-8 | | -2x=12-6x | | x​2​​−20x+100=0 | | 4–2p=2 | | (-2.9)x=-26.1 | | 2/3{x+3/5}=7/2 | | 10x+10+69=18x+15 | | 35=3x-11=23 | | 5(x+3)=4x-2 | | y/8+5=-9 | | 7p-5=5+1 | | 10((0.4+0.5g)=4g | | 9z-z=-3+2z-3-6 | | -5n-3-5=-8 | | (12/y)+(15/y)=3 | | 0.7x-0.1(16-5x)=0.8(x-8) | | (3x+14)=x |

Equations solver categories